PROTOTYPE SOLAR CELL BERBASIS TRANSISTOR TIPE MJ15003 MENGGUNAKAN SINGLE AXIS SOLAR TRACKER TERHADAP DAYA YANG DIHASILKAN - Fatria, Fatria (Politeknik Negeri Sriwijaya, 2019)
Energy usage is increasing every day with the growth of development in Indonesia. Electrical energy commonly used by the people of Indonesia comes from power plants that use fossil fuels. Sunlight can be electrical energy by using photovoltaic technology. In the discovery of solar energy there are factors that affect power. Surya's panel gets transistor main material MJ15003 as much 96 numbers. The operation of the solar cell depends on various things that will also affect the resulting power including a radiation intensity, titl of inclination and comparison of parallel and series circuit in transistors. On observational based on the radiation intensity is gotten energy big as 4.58–5.14 Watt. In the experiment with the optimum tilt of using single axis solar tracker is 59° and tilt without single axis solar tracker is 50°, obtained power increase in 11.5% of the use solar tracker. Based on the results and calculation of the magnitude of the resources obtained do not much different on the transistor with the order series and parallel circuits. In series with the value of the highest power 3.06 Watt and on a parallel series of 3.05 Watt.